Determinação do estádio ótimo de maturação a colheita do limão ‘siciliano’, produzidos no Estado do Ceará - Almeida, Mariana Benigno de (2014)
The state of Ceará is gaining attention as an emerging state in fruit production in the country. Lemons 'Sicilians', traditionally grown in the south, has been planted in this region, however, there still exist a lot of information about the quality of fruits grown locally. Lemon ‘Siciliano’ hybrid 'Eureka' is a non-climacteric fruit, should be harvested, bought and traded with their quality attributes related to the ideal flavor for consumption. The study aimed to determine the proper stage of maturity lemon ‘Siciliano’ at harvest through physical and physicochemical periodic measurements during development and fruit growth. Two experiments were conducted, following two separate flowerings. The first four samples were taken every 15 days and from the 49th day, the crops became every 7 days until the 91 th day being thus held a total of 11 samples at 0, 14, 28, 42 , 49, 56, 63, 70, 77, 84 and 91 days. . At each time, a total of 20 fruits were divided into 4 groups were collected and, thus, five replicates. The first experiment was conducted from October 2012 to January 2013 and the second in the months from July to October 2013. Fruits were assessed for physical and physicochemical characteristics: fresh weight, longitudinal and transverse diameters (DL / DT), format index, firmness of the peel, juice yield, thickness of the peel, color (h*, C* and L*) and chlorophyll content of the peel, pH, titratable acidity (TA), soluble solids (SS), SS/TA relationship and ascorbic acid content. An increase (p ≤ 0.05) of the variables: fresh weight, DL, DT and juice yield, in both experiments, was observed, while the color parameters of pH, L* and C* increased only in the first and SS in the second. Already, the variables chlorophyll and firmness of the peel decreased significantly, in both experiments, whereas the color parameter h* and ascorbic acid content decreased only in the first experiment and thickness of the peel, only the second. Thus, the end of the study of the development of lemons, it is concluded that the fruits were able to be picked at its optimum stage to harvest maturity after 77º days.